Ginkgo Biloba Bioactive Phytochemicals against Age-Related Diseases: Evidence from a Stepwise, High-Throughput Research Platform - Yuming Yuan; Xiaoyan Xiang; Xuejun Jiang; Yingju Liu; Ming Zhang; Luyang Lu; Xinping Zhang; Xinyi Liu; Qunyou Tan; Jingqing Zhang (Antioxidants)
The seeds of ginkgo biloba L (GB) have been widely used worldwide. This study investigated the bioefficacies of whole GB seed powder (WGP) retaining the full nutrients of ginkgo against aging, atherosclerosis, and fatigue. The experimental results indicated that WGP lowered brain monoamine oxidase and serum malondialdehyde levels, enhanced thymus/spleen indexes, and improved learning ability, and delayed aging in senescent mice. WGP regulated lipid levels and prevented atherosclerosis by reducing triglycerides, lowering low-density lipoprotein cholesterol, increasing high-density lipoprotein cholesterol, and decreasing the atherosclerosis index. WGP improved exercise performance by reducing blood lactate accumulation and extending exhaustive swimming and climbing times, improved energy storage by increasing muscle/liver glycogen levels, and relieved physical fatigue. Network pharmacology analysis revealed 270 potential targets of WGP that play roles in cellular pathways related to inflammation inhibition, metabolism regulation, and anti-cellular senescence, etc. Protein-protein interaction analysis identified 10 hub genes, including FOS, ESR1, MAPK8, and SP1 targets. Molecular docking and molecular dynamics simulations showed that the bioactive compounds of WGP bound well to the targets. This study suggests that WGP exerts prominent health-promoting effects through multiple components, targets, and pathways.